IMPLEMENTASI TEORI KONSTRUKTIVISME DALAM PAI: KAJIAN TEORI JEAN PIAGET DAN JEROME BRUNER - Mandar, Yasri; sihono, Sihono (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to analyze the implementation of constructivist theory in Islamic Religious Education (PAI) based on the ideas of Jean Piaget and Jerome Bruner. Employing a library research method with a descriptive-analytical approach, it explores how constructivism can enrich instructional strategies in PAI. The findings reveal that Piaget’s theory emphasizes the importance of cognitive development stages in learning, while Bruner highlights mental representation through direct experience, visualization, and symbolism. The application of constructivist theory enables students to develop a more reflective and contextual understanding of Islamic teachings. The study implies that PAI teachers should act as facilitators, encouraging dialogic and exploratory learning. However, a key limitation lies in its theoretical nature without empirical testing in classroom settings. Therefore, future research should focus on developing and practically testing constructivist-based instructional models and providing targeted training for educators to implement this approach effectively. Such efforts would help foster learners who are not only cognitively competent but also strong in spiritual and moral values.